Plasmonic nanograting enhanced quantum dots excitation for cellular imaging on-chip. (21st August 2015) - Bhave, Gauri; Lee, Youngkyu; Chen, Peng; Zhang, John X J
Abstract: We present the design and integration of a two-dimensional (2D) plasmonic nanogratings structure on the electrode of colloidal quantum dot-based light-emitting diodes (QDLEDs) as a compact light source towards arrayed on-chip imaging of tumor cells. Colloidal quantum dots (QDs) were used as the emission layer due to their unique capabilities, including multicolor emission, narrow bandwidth, tunable emission wavelengths, and compatibility with silicon fabrication. The nanograting, based on a metal-dielectric-metal plasmonic waveguide, aims to enhance the light intensity through the resonant reflection of surface plasmon (SP) waves. The key parameters of plasmonic nanogratings, including periodicity, slit width, and thicknesses of the metal and dielectric layers, were designed to tailor the frequency bandgap such that it matches the wavelength of operation. We fabricated QDLEDs with the integrated nanogratings and demonstrated an increase in electroluminescence intensity, measured along the direction perpendicular to the metal electrode. We found an increase of 34.72% in QDLED electroluminescence intensity from the area of the pattern and an increase of 32.63% from the photoluminescence of QDs deposited on a metal surface. We performed ex vivo transmission-mode microscopy to evaluate the nucleus–cytoplasm ratios of MDA-MB 231 cultured breast cancer cells using QDLEDs as the light source. We showed wavelength dependent imaging of different cell components and imaging of cells at higher magnification using enhanced emission from QDLEDs with integrated plasmonic nanogratings.